HELIUM ISOTOPES, TECTONICS AND HEAT FLOW IN THE NORTHERN CAUCASUS - Polyak B.G.; Yakovlev L.E.; Tolstikhin I.N.; Kamensky I.L.; Marty B.; Cheshko A.L. (My University, 2000)
109 new measurements of ³He/⁴He ≡ R in subsurface fluids of the Northern Caucasus coupled with the data obtained previously allow regional regularities in the distribution of helium isotopic composition to be examined. Cis-Caucasian foredeeps show the lowest radiogenic R-values. The average Rav-value is slightly higher in gases of the Scythian plate beyond the Stavropol arch. Within the arch, elevated R = (1.6–4.5) × 10⁻⁷ indicates an input of mantle-derived helium. This input is even more evident to the south of Starvropol arch, in the Caucasian Mineral Water area, where the ≈8 Ma old laccolithes occur and R-values approach (5–11) × 10⁻⁷. The highest R-values, up to (0.7–0.9) × 10⁻⁵, are observed further to the south, in the central segment of the Greater Caucasus, where recent volcanism is manifested. Enhanced R-values do not correlate with the crustal thickness but reflect degassing of magmatic reservoirs including those yet unknown.